Pengaruh konten review pada aplikasi tiktok terhadap minat beli produk somethinc di kalangan followers - Haliza, Happy Naja; Chasana, Rona Rizkhy Bunga (Universitas Garut, 2026)
Abstract In today's digital era, TikTok social media serves not only as an entertainment platform, but also as a source of information that influences consumer behavior, particularly in the skincare product category. Review content created by users based on their firsthand experience with a product is considered more trustworthy than other sources of information, as it is perceived to be more honest and authentic. This study aims to analyze the influence of TikTok review content on purchasing interest in skincare products, using a quantitative approach with a survey method of 100 respondents selected using a random sampling technique from followers of the @somethincofficial account on TikTok. Data collection was carried out through a questionnaire with a Likert scale of 1–4 to measure the variables of TikTok review content (X) and purchasing interest (Y). The data were then analyzed using the SPSS program version 25 through a simple linear regression test, t-test, and coefficient of determination. The results showed a regression coefficient value of 0.275 with a significance value of 0.000 <0.05 and a calculated t-value of 9.748 > 1.984, so the alternative hypothesis is accepted, which means that the more review content with positive values will further increase the purchasing interest of potential consumers. The final test, the coefficient of determination, showed an R-square of 49.2%. This indicates that TikTok review content has a positive influence on skincare product purchase interest, demonstrating that informative and credible review content on TikTok can increase consumer interest in purchasing Somethinc skincare products. Nevertheless, the magnitude of this influence also indicates that review content is not the sole factor shaping consumer purchase intention toward skincare products Keywords: Review content; TikTok, purchase intention, somethinc, S-O-R theory. Abstrak Di era digital saat ini, TikTok bukan hanya situs media sosial untuk hiburan, melainkan turut menjadi referensi data yang memberikan dampak signifikan terhadap perilaku konsumsi masyarakat, khususnya dalam kategori produk perawatan kulit. Konten review yang dibuat oleh pengguna berdasarkan pengalaman langsung menggunakan produk dinilai lebih dipercaya dibandingkan sumber informasi lainnya, karena dianggap lebih jujur dan autentik. Dengan menggunakan metode survei yang dipilih secara random dari pengikut akun @somethincofficial di TikTok, penelitian ini bertujuan untuk menganalisis pengaruh konten review di TikTok terhadap keinginan untuk membeli produk skincare. Untuk mengukur variabel konten review TikTok (X) dan minat beli (Y), pengumpulan data dilakukan melalui kuesioner dengan skala Likert 1–4. Selanjutnya, data dianalisis menggunakan program SPSS versi 25 dengan menggunakan uji regresi linear sederhana, uji t, dan koefisien determinasi. Hasil penelitian menunjukkan bahwa koefisien regresi sebesar 0,275, dengan nilai signifikansi 0,000<0,05, dan nilai t hitung 9,748>1,984 sehingga hipotesis alternatif diterima, yang berarti semakin banyak konten review dengan nilai positif akan semakin meningkatkan minat beli calon konsumen. Pada uji terakhir yaitu koefisien determinasi menunjukkan hasil R square sebesar 49,2%. Hal ini menunjukkan konten review TikTok memiliki pengaruh positif terhadap minat beli produk skincare, memperlihatkan bahwa konten review yang informatif dan kredibel di TikTok dapat meningkatkan minat konsumen untuk membeli produk skincare Somethinc. Meskipun begitu, besaran pengaruh tersebut juga menunjukkan bahwa konten review bukan merupakan satu-satunya faktor yang membentuk minat beli konsumen terhadap produk skincare. Kata-kata kunci: Konten review; tiktok; minat beli; Somethinc; teori S-O-R.